Wavelet Methodology for Analyzing Internet Marketing Metrics in Managing the Product Policy of the Business Entity - Babichev, A.; Samorodov, B.; Lyashenko, V. (International Journal of Academic Information Systems Research, 2023)
The formation and development of economic relations requires a change in the approach to the disclosure of such ties. At the heart of this lies the need to pay attention to individual business entities. This is due to the fact that in the modern world it is economic agents (enterprises, firms, companies) that determine the overall economic development. Their effective functioning is directly related to the proper implementation of the relevant commodity policy. It is important to use various tools to achieve your goals. Among such tools in the work is Internet marketing. This tool allows you to evaluate the promotion of goods and services on the market, take into account the interests of buyers, assess the dynamics o f demand, and attract new potential customers. One of the conditions for the implementation of this approach is the evaluation of Internet marketing in the management of product polic y. The paper reveals research directions in related studies, considers metrics for analyzing economic dynamics. The author's understanding of the Internet marketing metrics from the point of view of achieving the necessary conditions for the implementation of the product policy is proposed. To do this, we use the wavelet methodology, in particular wavelet coherence. A specific example of the proposed approach is considered. The work uses visualization to present empirical data and the results obtained. It is based on the us e of graphs and charts. The results obtained can be used in the development of strategies for the implementation of commodity policy for any business entity.
Keywords: metrics; wavelet coherence